FRI0565-PC Comparative study of osteoporosis progression at patients with rheumatoid arthritis in remission treatment with leflunomid versus biological agents. (23rd January 2014) - Bumbea, A. M.; Bighea, A.; Traistaru, R.; Popescu, R.; Matei, D.; Marcu, R.
Abstract : Background: It is known that patients with rheumatoid arthritis have frequently associated osteoporosis, both within the context of the disease and due to the treatment with corticosteroids. Objectives: We are to evaluate the progression of osteoporosis at patients with rheumatoid arthritis and osteoporosis - in therapy with bisphosphonates, D3 vitamin and 500mg calcium daily-at two groups of patients; one group in remissive treatment with leflunomid versus the other group in treatment with biological agents. For this evaluation we have developed a retrospective study within a 5-year period of time, 2007-2012. Methods: We have analyzed a number of 48 patients split in two homogeneous groups – each with 24 patients; all the patients have been diagnosed with osteoporosis, T score in between -2, 5 and -4, 2 standard deviation. The A Group has received a treatment with 20 mg of leflunomid daily and non steroidal anti-inflammatory drugs. The B Group has received a treatment with biological agents: infliximab 3mg/kg in infusion at 2 months, etanercept 50mg weekly and adalimumab 40 mg once at two weeks. Both groups have received bisphosphonates in therapeutic doses being evaluated for osteoporosis. The median patients` age was of 52.1 of which only 38 patients were at the beginning of the postmenopausal study. There was evaluated the level of the disease activity by the 28 DAS score. We also mention that at 12 patients treated with leflunomid there was necessary corticosteroids therapy in doses of 16 mg per day with a diminishing level of 8 mg on a period of 2 up to 6 months; meanwhile there was necessary the pulse therapy with metilprednisolon 1 mg/kg at 6 patients for a period of 3 days. Patients in biological therapy did not need corticosteroids therapy. We evaluated a witness group of 14 patients with rheumatoid arthritis and osteopeny who received only the supplement with D3 and 500mg of Calcium per day. Results: The A group of study presented the maintenance of median of T score at -3, 1 standard deviation, and DAS 28 median was lowered from 4.2 to 3.6. The B Group of study presented the diminishing of the level of osteoporosis from a T score from -3.9 to 3.2; the median of 28 DAS was reduced from 4.2 to 3.1. These levels showed osteopeny a T score from -1.8 to -2.4 with a passing to osteoporosis at 6 patients who needed to receive bisphosphonates, and the DAS 28 score presented a raise from 2.9 la 3.4 Conclusions: The diminishing level of osteoporosis with 0.2 standard deviations per year at the group of patients in therapy with biologic agents as compared to the group treated with leflunomid proves the fact that despite the beginning of the first group with lower values it obtained better results in both reducing the level of disease activity and the pathogenic immune inflammatory context. The witness group of patients with osteopeny proves both the role played by the patients' age in the beginning of menopause at 4 patients as well as the presence of the immune inflammatory factor in generating osteoporosis to patients with rheumatoid arthritis. Disclosure of Interest: None Declared